Carbon quantum dot and flame-retardant biomass composite film as well as preparation method and application thereof

By preparing and modifying carbon quantum dots, the problems of flammability of biomass films and poor flame retardant performance of traditional carbon quantum dots are solved, and the flame retardant performance of flame retardant biomass composite films are significantly improved, and its application in the field of high fire resistance requirements is expanded.

CN119875631AActive Publication Date: 2025-04-25HEBEI UNIV OF SCI & TECH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510050071.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-25
Estimated Expiration
2045-01-13

AI Technical Summary

Technical Problem

The flammability of biomass films limits its application in the field of high fire resistance requirements. Traditional carbon quantum dots have poor flame retardant performance and are difficult to achieve the optimal flame retardant state.

Method used

The hydrothermal reaction of urea and its derivatives, aminoglycerol compounds and aluminates was carried out to prepare a precursor with good chemical stability, and carbon quantum dots were prepared by solvothermal reaction, with surface modification to enhance their compatibility and binding strength with the substrate.

Benefits of technology

It significantly improves the flame retardant performance of carbon quantum dots, promotes the rapid formation of a stable carbon layer on the surface of the material, prevents heat and oxygen transfer, inhibits combustion, and reduces smoke generation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875631A_ABST
    Figure CN119875631A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of flame-retardant materials, and particularly discloses a carbon quantum dot and flame-retardant biomass composite film as well as a preparation method and application thereof. The preparation method comprises the following steps: taking urea and a derivative thereof as hydrogen bond donors, taking an aminoglycerol substance as a hydrogen bond receptor, and carrying out coordination binding with aluminate to obtain a precursor with good chemical stability; the precursor is used as a raw material, and the carbon quantum dots are prepared through solvothermal reaction. The flame-retardant film formed by the carbon quantum dots, the lignin and the cellulose is used for modifying a high-molecular polymer base material, so that the problems of poor compatibility and binding force between the lignin and the high-molecular polymer base material and between the cellulose and the high-molecular polymer base material are effectively solved; the flame-retardant effect of the biomass composite film is remarkably improved, meanwhile, the smoke yield during combustion of a high-molecular polymer base material is effectively inhibited, the application field of a high-molecular polymer material is expanded, and the biomass composite film has a wide application prospect in the flame-retardant field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of flame retardant materials, and in particular to a carbon quantum dot, a flame retardant biomass composite film and a preparation method thereof. Background Art

[0002] Polymer-based films are widely used in many fields due to their good flexibility, mechanical properties, barrier properties, etc. Among them, biomass films represented by cellulose and lignin, as an environmentally friendly polymer material, have many advantages such as being renewable, degradable, and biocompatible, and have shown broad application prospects in many fields such as food packaging, electronic devices, and agriculture. In the field of food packaging, it can effectively block oxygen and water vapor and extend the shelf life of food; in electronic devices, it can be used as a flexible substrate material to meet the development trend of electronic products becoming thinner and more flexible. However, biomass films themselves have a significant defect - flammability. This feature greatly limits its application in some scenarios with high fire protection requirements, such as in architectural decoration, aerospace, automotive interiors, etc. Once a fire occurs, biomass films are easily ignited and the fire spreads rapidly, causing serious safety hazards.

[0003] As a new type of carbon nanomaterial, carbon quantum dots have attracted much attention in the field of materials science in recent years. Carbon quantum dots are usually composed of carbon elements, with a size of nanometers and unique optical, electrical and chemical properties. Carbon quantum dots can undergo a series of complex physical and chemical changes during heating, such as decomposition to produce non-flammable gases, dilute the surrounding oxygen concentration, and form a dense carbon layer to isolate heat transfer and oxygen diffusion, thereby playing a flame retardant role. However, the research on the application of carbon quantum dots in polymer-based flame retardant films is still immature, and carbon quantum dots are very easy to agglomerate in the film due to their small size and high surface energy, which will lead to huge differences in the local flame retardant properties of the film, greatly reducing the fireproof reliability of the entire film. At present, the flame retardant properties of traditional carbon quantum dots are poor, and it is often difficult to make the film reach the optimal flame retardant state. Therefore, it is necessary to provide a new type of carbon quantum dots that can significantly improve the flame retardant properties of the film to expand the application scope of biomass films in fields with high fire protection requirements. Summary of the invention

[0004] In view of the problems in the prior art of poor flame retardancy of carbon quantum dots applied to high molecular polymer-based films, the present invention provides a carbon quantum dot, a flame retardant biomass composite film and a preparation method.

[0005] In order to solve the above technical problems, the technical solution provided by the present invention is:

[0006] A carbon quantum dot, wherein the preparation method of the carbon quantum dot comprises the following steps:

[0007] S1, subjecting urea and its derivatives, aminoglycerol compounds and aluminate to a hydrothermal reaction to obtain a precursor solution;

[0008] S2, mixing the precursor solution and the alcohol solvent evenly, performing a solvothermal reaction, and performing solid-liquid separation to obtain a carbon quantum dot solution.

[0009] Compared with the prior art, the carbon quantum dots provided by the present invention use urea and its derivatives as hydrogen bond donors, aminoglycerol substances as hydrogen bond acceptors, and then coordinate with aluminates to obtain a precursor with good chemical stability; the precursor is used as a raw material, and the carbon quantum dots are prepared by solvent thermal reaction. The surface of the carbon quantum dots prepared by the above method is modified with rich functional groups, such as amino, hydroxyl and other functional groups, which can not only improve the compatibility and binding force between the carbon quantum dots and the substrate material, but also participate in the reaction during the combustion process, play the role of capturing free radicals and promoting the formation of carbon layers, thereby enhancing the flame retardant effect; at the same time, the surface of the prepared carbon quantum dots has modified aluminate groups, and during the combustion process, aluminum elements can form stable substances such as aluminum oxide, which produce synergistic flame retardant effects with carbon quantum dots, further improving the flame retardant properties of the material. At the same time, the carbon quantum dots provided by the present invention can promote the rapid formation of a stable carbon layer on the surface of the material, prevent heat and oxygen from being transferred to the inside of the material, inhibit further combustion of the material, and reduce the generation of smoke. In addition, the preparation method of the carbon quantum dots is simple and easy, the preparation process is green and environmentally friendly, suitable for large-scale production and application, and has broad application prospects.

[0010] Furthermore, the urea and its derivatives include at least one of urea, isobutylene diurea or uric acid.

[0011] Furthermore, the aminoglycerol compound includes one or both of 3-amino-1,2-propylene glycol and 3-dimethylamino-1,2-propylene glycol.

[0012] Furthermore, the aluminate includes at least one of cobalt aluminate, calcium aluminate or sodium aluminate.

[0013] The carbon quantum dots prepared using the above-mentioned preferred urea and its derivatives, aminoglycerol compounds and aluminates as raw materials have a larger specific surface area and a smaller particle size, which is conducive to better dispersion in flame retardant materials and is not easy to agglomerate, thereby helping to give full play to the flame retardant effect of the carbon quantum dots and avoid problems such as poor local flame retardant effect caused by agglomeration; at the same time, the surface of the carbon quantum dots can also be modified with amino, hydroxyl and carboxyl groups to improve the compatibility and bonding strength of the carbon quantum dots with a variety of substrates, and can also participate in the reaction during the combustion process to promote the formation of a carbon layer and improve the flame retardant effect.

[0014] Furthermore, the molar ratio of the urea and its derivatives, the aminoglycerol compound and the aluminate is 1:1:0.05 to 1:5:1.

[0015] Furthermore, in S1, the temperature of the hydrothermal reaction is 60° C. to 130° C., and the time of the hydrothermal reaction is 0.5 h to 3 h.

[0016] Furthermore, in S2, the volume ratio of the precursor solution to the alcohol solvent is 1:30 to 1:40.

[0017] Furthermore, in S2, the solvent thermal reaction time is 180°C to 230°C, and the reaction time is 10h to 18h.

[0018] Furthermore, in S2, the alcohol solvent is anhydrous ethanol.

[0019] In a second aspect, the present invention also provides a flame retardant biomass composite film, comprising the carbon quantum dots, lignin and cellulose.

[0020] The film prepared with lignin and cellulose as raw materials has a rich intramolecular and intermolecular hydrogen bond network structure, which can make the film have good strength and toughness. However, lignin and cellulose have high crystallinity, strong polarity, and large surface energy. When added to the polymer material system as flame retardant materials, their compatibility with the substrate is poor, resulting in a significant impact on the flame retardant performance. The present invention uses nano-scale carbon quantum dots to modify lignin and cellulose films, enhances the contact area between lignin and cellulose and the polymer substrate, enhances the affinity of the two, improves the compatibility of the two, and helps to maximize the flame retardant effect of the flame retardant material.

[0021] There is a synergistic effect between lignin, cellulose and carbon quantum dots. Lignin and cellulose can both undergo carbonization reaction during the combustion process to form a carbon layer. Carbon quantum dots can promote the carbonization process of these two substances, making the carbon layer denser and more stable. The carbon layer has good heat insulation and oxygen isolation effects, which can effectively prevent heat and oxygen from transferring into the film, inhibit further combustion, and thus significantly improve the flame retardant properties of the film. At the same time, both lignin and cellulose have rich functional groups such as hydroxyl groups, which can interact with the functional groups on the surface of carbon quantum dots to form a stable composite structure, so that the three are evenly dispersed in the film, play a synergistic role, avoid phase separation, and improve the stability of the film's flame retardant properties.

[0022] Furthermore, the lignin is one or both of alkaline lignin and sodium lignin sulfonate; and the cellulose is at least one of carboxymethyl cellulose, cellulose acetate or microcrystalline cellulose.

[0023] In a third aspect, the present invention also provides a method for preparing a flame retardant biomass composite film, comprising the following steps:

[0024] The carbon quantum dots, lignin and cellulose are uniformly mixed and reacted at 40° C. to 100° C. for 0.5 h to 2 h to obtain a flame retardant film solution;

[0025] The flame retardant film solution is dried to obtain a flame retardant biomass composite film.

[0026] The method for preparing a flame-retardant biomass composite film provided by the present invention comprises the following steps: reacting carbon quantum dots, lignin and cellulose at a specific temperature so that the amino groups of the carbon quantum dots react with the hydroxyl groups of the cellulose, etc., and grafting the carbon quantum dots onto a film of cellulose and lignin, thereby improving the dispersion uniformity of the carbon quantum dots in the film, and greatly increasing the affinity of the cellulose and lignin grafted with the carbon quantum dots to a high molecular polymer substrate, thereby significantly improving the flame retardancy of the high molecular polymer substrate.

[0027] In a fourth aspect, the present invention further provides a high molecular polymer-based flame retardant material, comprising a high molecular polymer substrate and the flame retardant biomass composite film.

[0028] In a fifth aspect, the present invention also provides a method for preparing a polymer-based flame retardant material, comprising the following steps:

[0029] The flame retardant film solution and the curing agent are mixed evenly, coated on a high molecular polymer substrate, and dried to obtain a high molecular polymer-based flame retardant material.

[0030] The cellulose flame-retardant film provided by the present invention can significantly improve the thermal stability of the polymer substrate. When a fire occurs, it can decompose to form a stable, dense and uniform carbide covering the surface of the substrate, isolating heat, oxygen and other volatile gases, and inhibiting the spread of the fire. The biomass flame-retardant film can significantly improve the flame retardant properties of the polymer substrate and expand the application field of the polymer.

[0031] Furthermore, the curing agent is m-phenylenediamine; and the mass ratio of the curing agent to the flame retardant film solution is 1:10 to 1:40.

[0032] Furthermore, the mass ratio of the flame retardant film solution to the high molecular polymer substrate is 1:20 to 1:100.

[0033] The present invention uses a flame retardant film formed by carbon quantum dots, lignin and cellulose to modify the high molecular polymer material, which effectively solves the problems of poor compatibility and bonding between lignin, cellulose and polymer materials, and significantly improves the flame retardant effect of the biomass composite film through the synergistic effect between carbon quantum dots and lignin and cellulose. At the same time, it also effectively suppresses the smoke production during combustion of the high molecular polymer substrate, which is beneficial to expanding the application field of the high molecular polymer material. The raw material source is wide, the preparation process is simple, and it is suitable for large-scale production and application, and has broad application prospects in the flame retardant field. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a transmission electron microscope image of carbon quantum dots prepared in Example 2 of the present invention;

[0035] Figure 2 This is a scanning electron microscope image of the flame retardant biomass composite film prepared in Example 2 of the present invention;

[0036] Figure 3 This is a Fourier infrared spectrum of the flame retardant biomass composite film prepared in Example 2 of the present invention.

[0037] Figure 4 This is a comparison diagram of the relationship between the heat release rate and time of the original epoxy resin and the flame retardant epoxy resin in Example 2 of the present invention;

[0038] Figure 5 This is a comparison chart of the total heat release amount and time of the original epoxy resin and the flame retardant epoxy resin in Example 2 of the present invention. DETAILED DESCRIPTION

[0039] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0040] In order to better illustrate the present invention, further examples are given below.

[0041] Example 1

[0042] The embodiment of the present invention provides a carbon quantum dot, comprising uric acid, 3-amino-1,2-propanediol and calcium aluminate in a molar ratio of 1:5:1, and the preparation thereof specifically comprises the following steps:

[0043] 0.1 mol of uric acid, 0.5 mol of 3-amino-1,2-propanediol and 0.1 mol of calcium aluminate were mixed evenly, heated to 120°C, and stirred at constant temperature for 2 hours to obtain a precursor solution;

[0044] Take 2 mL of the above precursor solution, add it to 70 mL of anhydrous ethanol, heat it to 200° C. and react for 14 h. After centrifugation, filter it through a 0.22 μm filter membrane to obtain a carbon quantum dot solution.

[0045] The method for preparing a flame retardant biomass composite film using the above carbon quantum dot solution comprises the following steps:

[0046] 30 g of the carbon quantum dot solution prepared above, 0.2 g of alkaline lignin and 0.8 g of cellulose acetate were added into a three-necked bottle, heated to 45° C. and subjected to ultrasonic reaction for 2 h to obtain a flame retardant film solution, and the flame retardant film solution was dried to obtain a flame retardant biomass composite film.

[0047] The method for preparing a flame retardant epoxy resin using the flame retardant biomass composite film comprises the following steps:

[0048] 20 g of the flame retardant film solution prepared above and 0.7 g of m-phenylenediamine were mixed evenly, coated on 500 g of epoxy resin, and dried to obtain a flame retardant epoxy resin.

[0049] The flame retardant epoxy resin prepared in this embodiment was tested by an oxygen index tester, and its limiting oxygen index was 31.1%, which met the flame retardant requirement. Its combustion grade reached UL-94V-0 by a vertical combustion tester. Compared with the original epoxy resin with a fire rating of UL-94V-2, it has been significantly improved.

[0050] The residual carbon rate was measured by thermogravimetric analyzer to be 21% and the initial decomposition temperature (T 5% ) is 391℃, and the maximum decomposition temperature (T max ) is 421℃.

[0051] The total heat release was determined by cone calorimetry to be 80 MJ / m 2 The maximum heat release rate peak is 550kW / m 2 , the total smoke volume is 16m 2 / kg. Compared with the original epoxy resin, the total heat release (120MJ / m 2 ) decreased by 33.3%, and the maximum heat release rate peak (1102kW / m 2 ) decreased by 50.1%, and the total smoke volume (24m 2 / kg) decreased by 33.3%.

[0052] Example 2

[0053] The embodiment of the present invention provides a carbon quantum dot, comprising urea, 3-amino-1,2-propylene glycol and cobalt aluminate in a molar ratio of 1:3:0.5, and the preparation thereof specifically comprises the following steps:

[0054] 0.1 mol urea, 0.3 mol 3-amino-1,2-propylene glycol and 0.05 mol cobalt aluminate were mixed evenly, heated to 100° C., and stirred at constant temperature for 2 h to obtain a precursor solution;

[0055] Take 2 mL of the above precursor solution, add it to 80 mL of anhydrous ethanol, heat it to 210° C. and react for 16 h. After centrifugation, filter it through a 0.22 μm filter membrane to obtain a carbon quantum dot solution.

[0056] The transmission electron microscopy image of the carbon quantum dots prepared in this example is as follows Figure 1 As shown in the figure, it can be seen that the carbon quantum dots are spherical in shape, with relatively uniform particle size, an average particle size of 2nm, and are evenly distributed.

[0057] The method for preparing a flame retardant biomass composite film using the above carbon quantum dot solution comprises the following steps:

[0058] 30 g of the carbon quantum dot solution prepared above, 0.2 g of alkaline lignin and 0.8 g of cellulose acetate were added into a three-necked bottle, heated to 75° C. and subjected to ultrasonic reaction for 30 min to obtain a flame retardant film solution, and the flame retardant film solution was dried to obtain a flame retardant biomass composite film.

[0059] The scanning electron microscope image of the flame retardant biomass composite film prepared in this example is as follows Figure 2 As shown in the figure, it can be seen that the carbon quantum dots are successfully loaded onto the film. The infrared spectrum of the flame retardant biomass composite film is shown in Figure 3 As shown, 3425cm -1 The absorption peak at 2906cm is attributed to the characteristic peak of -OH vibration. -1 The peak at 1637cm is attributed to the CH bond. -1 The absorption peak at 1460 cm belongs to the amide group. -1 The absorption peak at 1095cm is attributed to CNC stretching vibration. -1 The absorption peak of CO bond is at , which indicates that the addition of carbon quantum dots in the film makes the surface of the film have rich functional groups.

[0060] The method for preparing a flame retardant epoxy resin using the flame retardant biomass composite film comprises the following steps:

[0061] 20 g of the flame retardant film solution prepared above and 2 g of m-phenylenediamine were mixed evenly, coated on 2000 g of epoxy resin, and dried to obtain a flame retardant epoxy resin.

[0062] The flame retardant epoxy resin prepared in this embodiment was tested by an oxygen index tester, and its limiting oxygen index was 33.1%, which met the flame retardant requirements. The combustion performance level was measured by a vertical combustion tester and reached UL-94V-0. Compared with the original epoxy resin, the fire rating was UL-94V-2, which was significantly improved. The residual carbon rate was measured by a thermogravimetric analyzer, and the initial decomposition temperature (T 5% ) is 418℃, the maximum decomposition temperature (T max ) is 452℃.

[0063] The actual combustion condition of the flame retardant epoxy resin prepared in this example was measured by cone calorimeter. Figure 4 and Figure 5The following are the comparison diagrams of the total heat release and heat release rate of the original epoxy resin and the flame retardant epoxy resin with respect to time. Figure 4 It can be seen that the total heat release of the original epoxy resin is 120MJ / m 2 The maximum heat release rate peak is 1102kW / m 2 kW / m 2 The total smoke volume is 24m 2 / kg. The total heat release after flame retardant epoxy resin is 75MJ / m 2 The maximum heat release rate peak is 414kW / m 2 The total smoke volume is 13m 2 / kg. Compared with the original epoxy resin, the flame retardant performance of the flame retardant epoxy resin was significantly improved, the total heat release decreased by 37.5%, the maximum heat release rate peak decreased by 62.4%, and the total smoke generation decreased by 45.8%.

[0064] Example 3

[0065] The embodiment of the present invention provides a carbon quantum dot, comprising isobutylene diurea, 3-dimethylamino-1,2-propylene glycol and cobalt aluminate in a molar ratio of 1:2:0.3, and the preparation thereof specifically comprises the following steps:

[0066] 0.1 mol of isobutylene diurea, 0.2 mol of 3-dimethylamino-1,2-propylene glycol and 0.03 mol of cobalt aluminate were mixed evenly, heated to 130° C., and stirred at constant temperature for 1 hour to obtain a precursor solution;

[0067] Take 2 mL of the above precursor solution, add it to 75 mL of anhydrous ethanol, heat it to 220° C. and react for 15 h. After centrifugation, filter it through a 0.22 μm filter membrane to obtain a carbon quantum dot solution.

[0068] The method for preparing a flame retardant biomass composite film using the above carbon quantum dot solution comprises the following steps:

[0069] 30 g of the carbon quantum dot solution prepared above, 0.2 g of alkaline lignin and 0.8 g of cellulose acetate were added into a three-necked bottle, heated to 100° C. and ultrasonically reacted for 30 min to obtain a flame retardant film solution, and the flame retardant film solution was dried to obtain a flame retardant biomass composite film.

[0070] The method for preparing a flame retardant epoxy resin using the flame retardant biomass composite film comprises the following steps:

[0071] 20 g of the flame retardant film solution prepared above and 1.8 g of m-phenylenediamine were mixed evenly, coated on 1600 g of epoxy resin, and dried to obtain a flame retardant epoxy resin.

[0072] The flame retardant epoxy resin prepared in this embodiment was passed through an oxygen index tester, and its limiting oxygen index was measured to be 30%, which met the flame retardant requirement. The combustion performance level was measured by a vertical combustion tester and reached UL-94V-0 level. Compared with the original epoxy resin fire rating of UL-94V-2 level, it has been significantly improved.

[0073] The residual carbon rate was measured by thermogravimetric analyzer to be 29% and the initial decomposition temperature (T 5% ) is 389℃, the maximum decomposition temperature (T max ) is 425°C. The total heat release measured by cone calorimeter is 84 MJ / m 2 The maximum heat release rate peak is 469kW / m 2 , the total smoke volume is 18m 2 / kg. Compared with the original epoxy resin, the total heat release (120MJ / m 2 ) decreased by 30%, and the maximum heat release rate peak (1102kW / m 2 ) decreased by 57.4%, and the total smoke volume (24m 2 / kg) decreased by 25%.

[0074] Example 4

[0075] The embodiment of the present invention provides a carbon quantum dot, comprising urea, 3-amino-1,2-propanediol and calcium aluminate in a molar ratio of 1:5:0.8, and the preparation thereof specifically comprises the following steps:

[0076] 0.1 mol urea, 0.5 mol 3-amino-1,2-propanediol and 0.08 mol calcium aluminate were mixed evenly, heated to 110°C, and stirred at constant temperature for 3 hours to obtain a precursor solution;

[0077] Take 2 mL of the above precursor solution, add it to 70 mL of anhydrous ethanol, heat it to 180° C. and react for 18 h. After centrifugation, filter it through a 0.22 μm filter membrane to obtain a carbon quantum dot solution.

[0078] The method for preparing a flame retardant biomass composite film using the above carbon quantum dot solution comprises the following steps:

[0079] 30 g of the carbon quantum dot solution prepared above, 0.2 g of alkaline lignin and 0.8 g of cellulose acetate were added into a three-necked bottle, heated to 60° C. and ultrasonically dispersed for 50 min to obtain a flame retardant film solution, and the flame retardant film solution was dried to obtain a flame retardant biomass composite film.

[0080] The method for preparing a flame retardant epoxy resin using the flame retardant biomass composite film comprises the following steps:

[0081] 20 g of the flame retardant film solution prepared above and 1.2 g of m-phenylenediamine were mixed evenly, coated on 800 g of epoxy resin, and dried to obtain a flame retardant epoxy resin.

[0082] The flame retardant epoxy resin prepared in this embodiment was passed through an oxygen index tester, and its limiting oxygen index was measured to be 33%, which met the flame retardant requirement. The combustion performance level was measured by a vertical combustion tester and reached UL-94V-0 level. Compared with the original epoxy resin fire rating of UL-94V-2 level, it has been significantly improved.

[0083] The residual carbon rate was measured by thermogravimetric analyzer to be 31.9% and the initial decomposition temperature (T 5% ) is 388℃, the maximum decomposition temperature (T max ) is 426°C. The total heat release measured by cone calorimeter is 68MJ / m 2 The maximum heat release rate peak is 390kW / m 2 , the total smoke volume is 17m 2 / kg. Compared with the original epoxy resin, the total heat release (120MJ / m 2 ) decreased by 43.3%, and the maximum heat release rate peak (1102kW / m 2 ) decreased by 64.6%, and the total smoke volume (24m 2 / kg) decreased by 29.2%.

[0084] Example 5

[0085] The embodiment of the present invention provides a carbon quantum dot, comprising uric acid, 3-amino-1,2-propanediol and sodium aluminate in a molar ratio of 1:1:0.05, and the preparation thereof specifically comprises the following steps:

[0086] 0.1 mol of uric acid, 0.1 mol of 3-amino-1,2-propanediol and 0.005 mol of sodium aluminate were mixed evenly, heated to 80°C, and stirred at constant temperature for 3 hours to obtain a precursor solution;

[0087] Take 2 mL of the above precursor solution, add it to 60 mL of anhydrous ethanol, heat it to 230° C. and react for 10 h. After centrifugation, filter it through a 0.22 μm filter membrane to obtain a carbon quantum dot solution.

[0088] The method for preparing a flame retardant biomass composite film using the above carbon quantum dot solution comprises the following steps:

[0089] 30 g of the carbon quantum dot solution prepared above, 0.2 g of alkaline lignin and 0.8 g of cellulose acetate were added into a three-necked bottle, heated to 85° C. and ultrasonically dispersed for 40 min to obtain a flame retardant film solution, and the flame retardant film solution was dried to obtain a flame retardant biomass composite film.

[0090] The method for preparing a flame retardant epoxy resin using the flame retardant biomass composite film comprises the following steps:

[0091] 20 g of the flame retardant film solution prepared above and 1.5 g of m-phenylenediamine were mixed evenly, coated on 900 g of epoxy resin, and dried to obtain a flame retardant epoxy resin.

[0092] The flame retardant epoxy resin prepared in this embodiment was passed through an oxygen index meter, and its limiting oxygen index was measured to be 32%, which met the flame retardant requirement. The combustion performance level was measured by a vertical combustion meter and reached UL-94V-0. Compared with the original epoxy resin fire rating of UL-94V-2, it has been significantly improved.

[0093] The residual carbon rate was measured by thermogravimetric analyzer and was 25%. The initial decomposition temperature (T 5% ) is 391℃, and the maximum decomposition temperature (T max ) is 427°C. The total heat release measured by cone calorimeter is 79MJ / m 2 The maximum heat release rate peak is 453kW / m 2 , the total smoke volume is 15m 2 / kg. Compared with the original epoxy resin, the total heat release (120MJ / m 2 ) decreased by 34.2%, and the maximum heat release rate peak (1102kW / m 2 ) decreased by 58.9%, and the total smoke volume (24m 2 / kg) decreased by 37.5%.

[0094] Comparative Example 1

[0095] This comparative example provides a carbon quantum dot, and its preparation method is different from that of Example 2 only in that the sodium aluminate in the precursor for preparing the carbon quantum dots in Example 2 is replaced with an equal amount of aluminum titanate, and the rest is exactly the same and will not be repeated here.

[0096] The method for preparing a flame retardant biomass composite film using the above carbon quantum dot solution comprises the following steps:

[0097] The above-prepared 30g carbon quantum dot solution, 0.2g alkaline lignin and 0.8g cellulose acetate were added to a three-necked bottle, heated to 75°C and ultrasonically dispersed for 30min to obtain a flame retardant film solution. The flame retardant film solution was dried, but a film could not be formed. Even if the ultrasonic mixing time or drying time was extended, a film could not be formed.

[0098] Comparative Example 2

[0099] This comparative example provides a carbon quantum dot, and the preparation method thereof is different from that of Example 2 in that the urea in the precursor for preparing the carbon quantum dots in Example 2 is replaced with an equal amount of ammonium bicarbonate, and the rest is exactly the same and will not be repeated here.

[0100] The method for preparing a flame retardant biomass composite film using the above carbon quantum dot solution comprises the following steps:

[0101] 30 g of the carbon quantum dot solution prepared above, 0.2 g of alkaline lignin and 0.8 g of cellulose acetate were added into a three-necked bottle, heated to 75° C. and ultrasonically dispersed for 30 min to obtain a flame retardant film solution, and the flame retardant film solution was dried to obtain a flame retardant biomass composite film.

[0102] The method for preparing a flame retardant epoxy resin using the flame retardant biomass composite film comprises the following steps:

[0103] 20 mL of the flame retardant film solution prepared above and 0.1 g of m-phenylenediamine were mixed evenly, coated on 4 g of epoxy resin, and dried to obtain a flame retardant epoxy resin.

[0104] The flame retardant epoxy resin prepared in this comparative example was tested by an oxygen index tester, and its limiting oxygen index was 28%, which met the flame retardancy requirement. The combustion performance grade was tested by a vertical combustion tester and reached UL-94V-1 grade.

[0105] The residual carbon rate was measured by thermogravimetric analyzer to be 16%, and the initial decomposition temperature (T 5% ) is 379℃, the maximum decomposition temperature (T max ) is 412°C. The total heat release measured by cone calorimeter is 110 MJ / m 2 The maximum heat release rate peak is 653kW / m 2 , the total smoke volume is 22m 2 / kg. Compared with the original epoxy resin, the fire rating of UL-94V-2 has been improved to a certain extent, but due to the large amount of dripping during the combustion process, it cannot meet the flame retardant performance requirements. In addition, in the flame retardant performance test, the total heat release and the peak value of the maximum heat release rate have been improved, but the total smoke volume (24m 2 / kg) was only reduced by 8.3%, and the smoke suppression effect was far worse than that of Examples 1-5.

[0106] Comparative Example 3

[0107] This comparative example provides a carbon quantum dot, and its preparation method is different from that of Example 2 only in that 3-dimethylamino-1,2-propanediol in the precursor for preparing the carbon quantum dots in Example 2 is replaced with an equal amount of 1,3-butanediol, and the rest is exactly the same and will not be repeated here.

[0108] The method for preparing a flame retardant biomass composite film using the above carbon quantum dot solution comprises the following steps:

[0109] 30 g of the carbon quantum dot solution prepared above, 0.2 g of alkaline lignin and 0.8 g of cellulose acetate were added into a three-necked bottle, heated to 75° C. and ultrasonically dispersed for 30 min to obtain a flame retardant film solution, and the flame retardant film solution was dried to obtain a flame retardant biomass composite film.

[0110] The method for preparing a flame retardant epoxy resin using the flame retardant biomass composite film comprises the following steps:

[0111] 20 mL of the flame retardant film solution prepared above and 0.1 g of m-phenylenediamine were mixed evenly, coated on 4 g of epoxy resin, and dried to obtain a flame retardant epoxy resin.

[0112] The flame retardant epoxy resin prepared in this example was tested by an oxygen index tester, and its limiting oxygen index was 26%, which did not meet the flame retardancy requirement. The combustion performance level was tested by a vertical combustion tester and reached UL-94V-1 level.

[0113] The residual carbon rate was measured by thermogravimetric analyzer to be 21%, and the initial decomposition temperature (T 5% ) is 383℃, the maximum decomposition temperature (T max ) is 427°C. The total heat release measured by cone calorimeter is 105 MJ / m 2 The maximum heat release rate peak is 816kW / m 2 , the total smoke volume is 20m 2 / kg.

[0114] In summary, the carbon quantum dots provided by the present invention have a simple preparation method and a wide range of raw material sources. The flame retardant biomass composite film prepared using the carbon quantum dots, lignin and cellulose has excellent flame retardant properties, can significantly improve the flame retardant properties of polymer materials, and expand the application of polymer materials in occasions with high fire protection requirements, and has high practical value.

[0115] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A carbon quantum dot, characterized in that The method for preparing carbon quantum dots comprises the following steps: S1, subjecting urea and its derivatives, aminoglycerol compounds and aluminate to a hydrothermal reaction to obtain a precursor solution; S2, mixing the precursor solution and the alcohol solvent evenly, performing a solvothermal reaction, and performing solid-liquid separation to obtain a carbon quantum dot solution.

2. The carbon quantum dot according to claim 1, characterized in that The urea and its derivatives include at least one of urea, isobutylene diurea or uric acid.

3. The carbon quantum dots according to claim 1, characterized in that The aminoglycerol compound includes one or both of 3-amino-1,2-propylene glycol and 3-dimethylamino-1,2-propylene glycol.

4. The carbon quantum dot according to claim 1, characterized in that The aluminate includes at least one of cobalt aluminate, calcium aluminate or sodium aluminate.

5. The carbon quantum dot according to any one of claims 1 to 4, characterized in that The molar ratio of the urea and its derivatives, the aminoglycerol compound and the aluminate is 1:1:0.05 to 1:5:

1.

6. The carbon quantum dot according to any one of claims 1 to 4, characterized in that In S1, the temperature of the hydrothermal reaction is 60°C to 130°C, and the time of the hydrothermal reaction is 0.5h to 3h; and / or In S2, the volume ratio of the precursor solution to the alcohol solvent is 1:30 to 1:40; and / or In S2, the solvent thermal reaction time is 180°C to 230°C, and the reaction time is 10h to 18h; and / or In S2, the alcohol solvent is anhydrous ethanol.

7. A flame retardant biomass composite film, characterized in that: The invention comprises the carbon quantum dots according to any one of claims 1 to 6, lignin and cellulose.

8. A method for preparing a flame retardant biomass composite film, characterized in that: The steps include: The carbon quantum dots, lignin and cellulose according to any one of claims 1 to 6 are uniformly mixed and reacted at 40° C. to 100° C. for 0.5 h to 2 h to obtain a flame retardant film solution; The flame retardant film solution is dried to obtain a flame retardant biomass composite film.

9. A polymer-based flame retardant material, characterized in that: It comprises a high molecular polymer substrate and the flame retardant biomass composite film as claimed in claim 7.

10. A method for preparing a polymer-based flame retardant material, characterized in that: The steps include: The flame retardant film solution and curing agent described in claim 8 are mixed evenly, coated on a high molecular polymer substrate, and dried to obtain a high molecular polymer-based flame retardant material.

Citation Information

Patent Citations

  • Fluorescent carbon quantum dot, fluorescent carbon quantum dot / cellulose nanocrystal composite film and preparation method of fluorescent carbon quantum dot / cellulose nanocrystal composite film

    CN115161023A

  • Lignin-based flame-retardant biodegradable polylactic acid film

    CN115418090A

  • Eutectic solvent as well as preparation method and application thereof

    CN116656352A

  • Eutectic solvent, preparation method thereof and application of eutectic solvent in flame-retardant material

    CN117362747A

  • Hybrid core-shell ferroferric oxide with flame-retardant and electromagnetic wave absorption functions, composite material of hybrid core-shell ferroferric oxide and preparation method of hybrid core-shell ferroferric oxide

    CN118638348A